Sejarah Lembaga Pendidikan Islam di Nusantara: Surau, Pesantren dan Madrasah - Silvia, Elvi (Pascasarjana IAIN Metro, 2023)
In the educational process, educational institutions play a very important role, because educational institutions function as places of learning. The exsitence of educational institutions will facilitate the process of acquiring knowledge. Islamic educational institutions in the archipelogo are surau, Islamic boarding school and madrasas. Surau and islamic boarding school are classical Islamic educational institutations and are also called true Islamic educational institutions (intigenius). The reason suraus and Islamic boarding schools are said to be genuine educational institutions is because they come from below and their model does not imitate other models, the model is unique tho the archipelogo. The aim of this reseach is to examine the history and dynamics of Islamic educational institutions in the archipelago, namely surau, Islamic boarding school and madasas. This reseach method uses a library reseach method whose reseach sources are from previois books and articles related to Islamic educational institutions in the archipelogo. The results of this reseach are that the introduction of Islamic teachings in the archipelogo cannot be separated from the influence of education. The begining of Islamic education began when Islam entered the archipelago in a simple form. Education has received top priority for the Islamic comunity in the archipelago since the begunning of the development of Islam. Because educatios has a very big meaning and can encourage muslim communities to practice Islamic teachings even though the system is still very simple. The teaching system which was carried out in places of warship such as mosques, surau and ulama`s houses which were also used as places of study. Educational institutions are very inportant in the development of Islamic education, because Islamic educational institutions in the archipelago can produce scholars who will teach the knowledge obtained from Islamic educational institutions to be taught to the public.